Comprovação do efeito antioxidante de plantas medicinais utilizadas no tratamento do diabetes mellitus em animais: Artigo de atualização - Dallaqua, B. [UNESP]; Damasceno, D. C. [UNESP] (My University, 2011)
Diabetes mellitus (DM) is a syndrome of multiple etiology characterized by chronic hyperglycemia. This hyperglycemia induces increased production of reactive oxygen species (ROS) and decreased antioxidant defenses. Due to complications caused by diabetes, a large number of people have chosen medicinal plant-based alternative therapies to alleviate its effects. Thus, in this literature review, several experimental studies with the use of diabetic animals were analyzed to demonstrate the antioxidant effects of these plants and to verify if the titles and abstracts provided in the papers are compatible with the aims of our search.
Evidence of the antioxidant effect of medicinal plants used in the treatment of diabetes mellitus in animals: An update
Keywords: Antioxidant; Diabetes; Plant; Rats